Strategi Guru Pendidikan Agama Islam (PAI) dalam Meningkatkan Minat Belajar Peserta Didik Perspektif Hamzah B Uno - Adi Widayat (Universitas Islam Tribakti Lirboyo Kediri, 2023)
Abstract This study aims to investigate the concept of Islamic Religious Education (PAI) teacher strategies in increasing students' learning interest, based on Hamzah B. Uno's perspective, as well as the influence of Islamic Religious Education teacher strategies on students' learning interest at SMK Mutu Tunjungmuli Purbalingga in 2021-2022. The research method used is qualitative by collecting data through observation, interviews, and documentation. The triangulation technique is used to verify the validity of the data, while the data analysis used is descriptive qualitative. The results showed that PAI teachers at SMK Mutu Tunjungmuli used various strategies, such as organizing using textbooks, picture media, and worksheets, delivering material using inquiry learning methods, lectures, discussions, and questions and answers, and managing learning using lesson plans and an emphasis on the importance of learning Islamic religious education. The implementation of this strategy has positive impacts, including increasing students' interest in participating in learning, increasing students' activeness in discussions and asking questions, and increasing students' final grades. This research provides a better understanding of the concept of PAI teacher strategy and its impact on students' learning interest, which can make a significant contribution to the development of Islamic religious education at SMK Mutu Tunjungmuli.